Scintillation-induced variability in radio absorption spectra against extragalactic sources - Macquart, Jean-pierre (EDP Sciences, 2005)
Spectral features absorbed against some radio quasars exhibit ~50 mJy variations, with the lines varying both relative to the continuum and, when several lines are present, even relative to one another. We point out that such variability can be expected as a consequence of refractive scintillation caused by the interstellar medium of our Galaxy. Scintillation can cause independent variations between closely-spaced spectral lines, and can even alter the line profile. The background source need not he compact to exhibit spectral variability. The variability can he used to infer the parsec to sub-parsec scale structure of the intervening absorbing material. We discuss the importance of scintillation relative to other possible origins of spectral variability. The present theory is applied to account for the variations observed in the HI-absorbed quasar PKS I 127-145.